Uji Bahan Organik Terlarut di Pelabuhan Kalbut Kabupaten Situbondo - Rinaldy Harjo Purnomo; Anita Diah Pahlewi (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2023)
The importance of waters as an economic resource, especially in the context of the organic material content that influences the life of marine organisms. The research focuses on the organic material content in the waters of Kalbut Beach, Situbondo Regency using the titrimetric method. The results showed significant differences in organic matter concentrations between the three water sampling points (R1, R2, R3), indicating potential pollutants in the region. This research shows that the organic matter content in seawater can be an important indicator for evaluating the level of pollution or sustainability of the aquatic environment. In particular, high values ​​may indicate the presence of pollutant sources such as industrial activity or waste disposal. This analysis also provides suggestions regarding the need for further investigation regarding pollutant sources in certain areas, increased control and monitoring of human activities, as well as management measures to maintain the quality of the aquatic environment. The results of this research can be used as a basis for concrete action in maintaining and improving sea water quality around Kalbut Harbor. With a deeper understanding of water quality, management and monitoring measures can be strengthened to maintain a better water environment, especially in areas with high concentrations of organic matter. This analysis provides important information about the condition of the water environment in each region which can be the basis for specific actions to improve sea water quality